The meaning of peer group mentoring in the university context - Terhi Skaniakos; Arja Piirainen (International journal of evidence based coaching and mentoring, 2019)
Peer mentoring is commonly used for didactical and learning purposes. In this study we examine peer group mentoring in the university context. The aim is to promote understanding of peer group mentoring based on a meta-analysis of two primary studies: teacher students and teacher group tutors. As a result, three core categories were found: 1) Individual’s participation in the group, 2) Professional development with others and 3) Community enabling sharing and development. These were hierarchically organized and there are critical aspects placed in between the core categories. Professional and personal experiences intertwine to enhance participants’ self-understanding and professional development.